International Market Entry Strategies: Exploring the Role of Institutional Environment in the Sweden - Nilsson, Alicia (European Journal of Business and Strategic Management, 2024)
Purpose: The aim of the study was to analyze the international market entry strategies: exploring the role of institutional environment in the Sweden. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Research on international market entry strategies in Sweden reveals that the institutional environment strongly influences multinational corporations' (MNCs) decisions. Factors like regulations, political stability, and cultural norms are key considerations. Adaptation to Sweden's unique socio-economic context is crucial for successful market entry. The findings emphasize the importance of MNCs assessing and navigating the institutional environment when devising their strategies in Sweden. Unique Contribution to Theory, Practice and Policy: Institutional theory, resource-based view (RBV) & transaction cost economics (TCE) may be used to anchor future studies on analyze the international market entry strategies: exploring the role of institutional environment in the Sweden. Firms aiming to enter the Swedish market should conduct thorough institutional analysis to understand the regulatory frameworks, cultural norms, and socio-political dynamics that may impact their market entry strategies. Policymakers in Sweden should strive to create a conducive institutional environment that facilitates foreign investment and market entry while maintaining regulatory stability and transparency.